Preparation and structures of cyclic tetrathiadienes and tetrathiaenynes - Stäb, Tobias; Gleiter, Rolf; Rominger, Frank (European journal of organic chemistry, 2002)
Through the use of diisobutylaluminium hydride (DIBAH) we were able to reduce selectively the triple bond(s) of the following cyclic diynes: 1,4,7,10-tetrathiacyclodeca-2,8-diyne (1), 1,4,8,11-tetrathiacyclotetradeca-2,9-diyne (2), 1,4,9,12-tetrathiacyclohexadeca-2,10-diyne (3), 1,4,10,13-tetrathiacyclooctadeca-2,11-diyne (4), 1,4,11,14-tetrathiacycloeicosa-2,12-diyne (5), 1,4,8,11-tetrathiacycloheptadeca-2,9-diyne (6), and 7,16-dioxa-1,4,10,13-tetrathiacyclooctadeca-2,11-diyne (7). The resulting cyclic enynes 8−14 and cyclic dienes 15−20 were isolated and characterized by their analytical data. In the cases of 8, 10, 11, 14, and 15−20 we were able to isolate single crystals, which were investigated by X-ray diffraction. For all molecular structures we found stair-like conformations. These shapes of the molecules were traced back to the zigzag arrangements of the hydrocarbon chains and the rigid building units (S−CH=CH−S) and/or (S−C≡C−S). In the solid-state forms of 11, 16, 17, and 19 we encountered columnar structures caused by close contacts between sulfur centers of neighboring rings. (© Wiley-VCH Verlag GmbH, 69451 Weinheim, Germany, 2002)
Gesehen am 27.10.2020